Exploring the Analytical Solutions to the Economical Model via Three Different Methods - M. Raheel; Khalid K. Ali; Asim Zafar; Ahmet Bekir; Omar Abu Arqub; Marwan Abukhaled (Journal of Mathematics)
In this article, the analytical solutions of economically important model named as the Ivancevic option pricing model (IOPM) along new definition of derivative have been explored. For this purpose, expa function, extended sinh-Gordon equation expansion (EShGEE) and extended G′/G-expansion methods have been utilized. The resulting solutions are dark, bright, dark-bright, periodic, singular, and other kinds of solutions. These solutions are obtained and also verified by a Mathematica tool. Some of the gained results are explained by 2-D, 3-D, and contour plots.